Using the adjuvants during infusion of local anaestetics into caudal-epidural space in newborns - M. Yu. Kurochkin (Zaporozhye State Medical University, 2012)
Markers of stress and central haemodynamics were investigated in 45 newborns. General anesthesia and caudal infusion of local anesthetics were combined in 15 newborns. Promedol and clonidine were added to local anesthetics in 15 newborns. Traditional ataralgesia was introduced in 15 newborns. Anesthesia with adjuvants showed The longest and finest effect.